Modulation of thermoelectric properties of Mg2GeO4 thin films by controlling the growth process. Issue 15 (15th October 2019) - Mahmood, K.; Jacob, Jolly; Rehman, A.; Ali, A.; Rehaman, U.; Amin, N.; Ikram, S.; Ashfaq, A.; Hussain, S.
Abstract: The aim of present study is to enhance the thermoelectric properties of Mg2 GeO4 thin films via controlling the growth mechanism by varying the source-substrate distance during the thermal evaporation process in tube furnace. The samples were grown using fixed pressure (2 × 10 -3 torr), oxygen flow rate (100 sccm), evaporation temperature (950 0 C) and varying source-substrate distance (5-15 cm). The XRD data demonstrated that sample grown using source-substrate distance 15 cm has best crystal structure while 5 cm sample has poor quality. The poor crystal quality is due to the presence of oxygen vacancy type defects. This dependence of crystal structure on source-substrate distance was also studied by Raman spectroscopy measurements. The Raman graph showed that sample grown using source-substrate distance 10 cm has amorphous structure because it has only Si peak at 521 cm -1 . But the Raman spectra of samples grown using 5 and 15 cm distances show peaks due to Raman modes of Mg2 GeO4 structure. Seebeck and Hall data suggested that Mg2 GeeO4 sample grown at 10 cm distance posses high values of Seebeck coefficient, electrical conductivity and power factor with values 1998 μV/ 0 C, 125 S/cm and 8.1 × 10 -3 Wm -1 K -2 respectively. These high values of thermoelectric properties are related with the higher carrier concentration of the sample grown using source-substrate distance 10 cm. This argument was further verified by Hall data which confirmed that his sample has highest electrical conductivity.